Hubungan Gaya Kepemimpinan Pengurus Harian dengan Loyalitas Anggota Aktif Organisasi di UK-Koperasi Mahasiswa Universitas Negeri Padang - Ari Suteja (Journal of Educational Administration and Leadership, 2020)
This Study aims to see the relationship between leadership style and the loyalty of active members of the organization in the tudent Cooperative, Padang State University. This type of research is correlational research. Population on this study included 109 active members and 54 samples using the simple random sampling technique. The research instrument used a questionnaire with a Likert scale model. The result of this study was that there was siginificant relationship between the leadership style of the daily administrators and the loyalty of active members of the organization in the Student Cooperative, Padang State University.